Illness remission status and commissural and associative brain white matter fiber changes in schizophrenia. Issue 6 (2nd September 2020) - Wong, Hong Jie; Chew, Qian Hui; Lee, Renick D.; Sim, Kang
Abstract: There is a paucity of studies clarifying biological basis of illness remission in schizophrenia related to white matter abnormalities, hence this study aimed to examine brain white matter anomalies via combinatorial diffusion tensor imaging (DTI) indices between remitted and nonremitted patients and evaluate predictors of remission. We examined DTI data of 178 patients who met the DSM‐IV criteria for schizophrenia (120 nonremitted, 58 remitted) and 111 healthy controls. Remission was determined using Global Assessment of Functioning (GAF) and Positive and Negative Syndrome Scale (PANSS) scores. Analysis of covariance identified significantly different white matter tracts between groups, whilst covarying for clinical variables. Correlation and regression analyses were performed to determine clinical‐imaging predictors of remission. Compared to controls, both nonremitted and remitted patients had reduced fractional anisotropy in the body of corpus callosum (BCC) and posterior thalamic radiation. Nonremitted patients had higher axial diffusivity (AD)/mean diffusivity (MD) values in the right cingulum than remitted patients after controlling for duration of illness, number of hospitalizations, and daily total chlorpromazine equivalents. The MD and AD of right cingulum correlated positively with the severity of psychotic psychopathology in nonremitted subjects. In addition, female sex and longer duration of illness were also significant predictors of remission. Specific DTI indices reflecting axonal processes and inflammation/edema of associative fibers (right cingulum) differentiated nonremitted from remitted patients, and together with relevant clinical factors, could serve as potential prognostic markers in schizophrenia.